Increased IgG4-positive plasma cells in nodular-sclerosing Hodgkin lymphoma: a diagnostic pitfall - Nowak, Verena; Agaimy, Abbas; Kristiansen, Glen; Gütgemann, Ines (Histopathology, 2019)
Aims: Despite increasing interest in the recently established immunoglobulin 4-related disease (IgG4-RD), its pathogenesis and aetiology remain largely unclear. Characteristic histopathological features are one of the key elements of diagnosis, including ‘storiform’ fibrosis, obliterative phlebitis, increased lymphoplasmacytic infiltration and increased levels of IgG4 in serum and tissue. Histopathological features of IgG4-RD are striking but not specific, and can pose a pitfall for surgical pathologists. This paper aims to determine the actual amount of IgG4+ plasma cells in nodular-sclerosing Hodgkin lymphoma (NSHL) and its potential to be misdiagnosed in routine clinical practice. Methods and results: IgG4+ plasma cells per high-power field (HPF) and the ratio of IgG4+ versus IgG+ plasma cells (IgG4/IgG ratio) in lymph node biopsies of 24 patients with nodular-sclerosing Hodgkin lymphoma (NSHL) were determined using immunohistochemistry and consensus scoring criteria as used for IgG4-RD. Ten lymph node biopsies with reactive follicular hyperplasia were assessed for comparison. Higher numbers of IgG4+ plasma cells (P < 0.001) were observed in NSHL versus follicular hyperplasia (mean 34 versus 8 per HPF) with a mean IgG4/IgG ratio of 0.38 versus 0.18. Five cases (21%) fulfilled the consensus criteria of IgG4-RD, with >50 IgG4+ plasma cells per HPF and an IgG4/IgG ratio of >0.4. The mean count of IgG4+ plasma cells per HPF in NSHL varied greatly (3–88) with increased numbers of IgG4+ plasma cells seen near areas of fibrosclerosis. Conclusions: Significantly higher levels of IgG4+ plasma cells are common in NSHL, emphasising the need to exclude Reed–Sternberg cells by morphology and immunohistochemistry in biopsies where IgG4-RD is suspected.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Hodgkin lymphoma; IgG4-related disease; IgG4/IgG ratio; nodular-sclerosing Hodgkin lymphoma